Analisis Parameter Lingkungan untuk Kesesuaian Wisata Pantai di Pantai Kuala Raja, Kabupaten Bireuen - Maulana, Andra (Jurnal Ilmu Kelautan Lesser Sunda, 2023)
Kuala Raja Beach is one of the beaches in Bireuen Regency which is one of the favorite tourist attractions of the surrounding community. The beauty that is on Kuala Raja Beach makes many enthusiasts who come from day to day to travel especially on holidays, therefore it is necessary to do a tourism suitability analysis in order to know the suitability of coastal tourism to the parameters that have been determined for a tourist area. This study aims to determine the state of environmental parameters for the suitability of Kuala Raja Beach tourism and analyze the suitability of Kuala Raja Beach based on the provisions of the tourist area. The method used during the research is a survey method in August 2022. The tourism suitability data to be taken are depth, current speed, brightness, beach width, beach type, beach slope, water base material, coastal land cover, distance of fresh water availability, dangerous biota, pH and salinity. This study uses descriptive data analysis with the results of measuring environmental parameters at Kuala Raja Beach at stations 1, 2 and 3 related to the tourism index, obtaining a percentage result with a value of 91.17% very suitable (S1). Overall Kuala Raja Beach is good for tourism activities, it's just that the depth at station 1 is deeper than the other 2 stations, and for beach recreation activities it is very suitable at station 3 because the width of the beach is very wide and more flexible to carry out activities.